THE PREVALENCE OF SEXUAL DYSFUNCTION AND URINARY INCONTINENCE AS PELVIC FLOOR DYSFUNCTION AND ASSOCIATED RISK FACTORS IN TURKISH WOMEN - Cayan, S.; Yaman, O.; Orhan, I; Usta, M.; Basar, M.; Resim, S.; Kadioglu, A. (Wiley-Blackwell, 2014)
[Abstract Not Available]